EKSISTENSI HUKU ¬M TERHADAP PENERBITAN AKTA KELAHIRAN ANAK DARI PERKAWINAN BAWAH TANGAN DI DISDUKCAPIL SINTANG - NIM. A1011201034, FITRI HARYANI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Underhand marriage is a marriage that is not recorded by the Office of Religious Affairs (KUA), but can be said to be religiously valid, but not legally valid in Indonesia. Families married under the status of an underhand marriage that causes the effect of the issuance of a child's birth certificate from the negligence of the parents in the process of making and the long or difficult process undertaken at the local DUKCAPIL. The problem studied in writing this thesis is